2017
DOI: 10.18256/2237-7956.2017.v7i2.1719
|View full text |Cite
|
Sign up to set email alerts
|

Competências Organizacionais no Contexto dos Relacionamentos Interorganizacionais

Abstract: As competências organizacionais exercem papel importante para o estabelecimento e desenvolvimento da estratégia corporativa. É por meio delas que os recursos e as capacidades são utilizados com vistas a aumentar a competitividade entre as organizações. As competências ainda podem ser adquiridas, aperfeiçoadas e customizadas por meio das relações interorganizacionais, onde verifica-se a colaboração, a coopetição e o compartilhamento de recursos. Portanto, a troca de conhecimento entre as organizações possibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…One of the key reasons for alliances to fail is how each of the parties involved manages them. Previous literature reviews identified that the development of interorganizational relationship competencies contributes to the sustainability of competitive advantage (e.g., Nascimento et al, 2017). Additionally, recent studies have shown that alliance management capability (AMC) is a fundamental precedent for the good performance of strategic alliances (Feller, Parhankangas, Smeds & Jaatinen, 2013;Schreiner, Kale & Corsten, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…One of the key reasons for alliances to fail is how each of the parties involved manages them. Previous literature reviews identified that the development of interorganizational relationship competencies contributes to the sustainability of competitive advantage (e.g., Nascimento et al, 2017). Additionally, recent studies have shown that alliance management capability (AMC) is a fundamental precedent for the good performance of strategic alliances (Feller, Parhankangas, Smeds & Jaatinen, 2013;Schreiner, Kale & Corsten, 2009).…”
Section: Introductionmentioning
confidence: 99%